High School Student-Athletes: Their Motivation, Study Habits, Self-Discipline, Academic Support, and Academic Performance - Dian Pujianto; Yahya Eko Nopiyanto; Cahyo Wibowo; Ipa Sari Kardi; Septian Raibowo; Bayu Insanistyo; Ibrahim; Baharuddin Hasan; Agus Sutriawan (OVS LLC, 2024)
Study purpose. Student-athletes have a role that is not easy to balance between the role of being an athlete and the role of being a student at school. Not a few of them have obstacles in balancing both roles. This study aims to reveal the characteristics of secondary school student-athletes in Bengkulu City. The main objectives are to describe the level of achievement motivation, study habits, self-discipline, academic support, and academic performance. Materials and methods. This study is a quantitative descriptive research with a survey approach involving 402 student-athletes at the junior high school and senior high school levels. The student-athletes represent 16 sports. The average age of  student-athletes is 15.9 years. The instrument used in the study was a questionnaire consisting of 36 statement items. The mean ideal and standard deviation ideal formulas were used to analyze data regarding the category level of each indicator, while the independent sample t-test was used to determine differences in data between student-athletes based on gender and type of sport. Results. The results of this study reveal that student-athletes in Bengkulu City have achievement motivation, study habits, self-discipline, academic support, and academic performance in the high category. There is a significant difference between male and female student-athletes (sig 0.001 < 0.005). There were no significant differences between student-athletes from individual and team sports (0.442 > 0.005). Conclusions. Student-athletes at junior high school and senior high school education levels have good characteristics, there are significant differences between male and female athletes, and there are no significant differences between individual athletes and team athletes.